Various Parameters Affecting to Production of Dried Jasminum sambac Flower - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Jasminum sambac is one of the most cultivated species in Vietnam. The plant is much valued for its exquisitely fragrant flowers. Flowers of Jasminum sambac have been utilized as traditional medicines to treat many diseases. Objective of this study focused on on the effectiveness of different parameters of freeze-drying such as pressure (0.06, 0.08, 0.10, 0.12 mbar), primary drying temperature (-3oC, -5oC, -7oC, -9oC) and secondary temperature (26oC, 28oC, 30oC, 32oC) to the total phenolic (mg GAE/100 g) and total flavonoid (mg QE/100 g) of dried Jasminum sambac flower. At the end of drying process, we also monitored the stability of dried Jasminum sambac flower during 6 months of preservation. Our results showed that the optimal drying process should be conducted at 0.08 mbar, primary drying temperature -7oC, secondary temperature 28oC to achieve the best dried Jasminum sambac flower. From this production, shelf-life of dried Jasminum sambac flower could be last for 6 months without any deterioration.Keywords: Jasminum sambac, Dried flower, Freeze-drying, Total phenolic, Total flavonoid, Shelf-life, preservation.